ANALYSIS OF THE PRINCIPAL'S LEADERSHIP STYLE IN IMPLEMENTING TEACHER DUTIES AT TIARA PRIVATE ELEMENTARY SCHOOL - Ivo Ardila; Ibnatun Salis; Winara; Wildansyah Lubis (STMIK Indonesia Banda Aceh, 2026)
Leadership style plays a crucial role in the quality of teacher performance in elementary schools. This study aims to analyze the principal's leadership style in the performance of teacher duties. The study used a descriptive qualitative approach and was conducted at Tiara Bandar Setia Private Elementary School in the even semester of the 2025-2026 academic year. Subjects were the principal and all 10 teachers from grades 1 to 6. Data collection was conducted through interviews and questionnaires. The results showed that teachers perceived an authoritarian leadership style of 0%, a democratic leadership style of 100%, and a laissez-faire leadership style, with freedom to make decisions (80%) and substantial autonomy in carrying out tasks (90%). However, all stated that the principal did not avoid responsibility, did not provide minimal direction, and still conducted regular performance evaluations (0%). Therefore, it was concluded that the dominant leadership style practiced by the principal at Tiara Bandar Setia Private Elementary School was democratic leadership, complemented by elements of functional laissez-faire leadership in the form of constructive professional trust.